ORGANIZATIONAL STRUCTURE AND MANAGEMENT UNDER THE CONTINGENCY THEORY PERSPECTIV - Cicero da Silva, Luciano; Henrique Ferreira Manso, Paulo; Henrique Ribeiro Beccari Silva, Pablo (Revista Gênero e Interdisciplinaridade, 2023)
This work is based on studies by Burns & Stalker (1960) and Lawrence & Lorsch (1967), who contributed with the use of the variable “environment” to define organizational structures in companies. In terms of the division of labor factor, the results confirmed that the organizational structure model is classified as a mechanical structure. In the other factors, the company presents evidence of the two models of structure, both mechanical and organic. It can be said that the findings corroborate the literature on the theory of contingency, which ensures that there is no single formula for managing a company.